Penerapan Hipnosis Lima Jari Pada Ibu Hamil Untuk Mengurangi Kecemasan Di Kelurahan Jagalan Surakarta - Melinda Ayu Anggraini; Exda Hanung Lidiana (Universitas Katolik Widya Karya Malang, 2023)
Pregnancy is a physiological phenomenon that begins with fertilization and ends with the birth process. During pregnancy, pregnant women experience many physical and psychological changes that cause anxiety. Anxiety can be overcome with self-hypnosis techniques for relaxation, which are carried out independently at home by incorporating positive programs, namely Five-Finger Hypnosis Therapy.This implementation design uses the case study method. The number of samples is 2 pregnant women who experience moderate anxiety and live in Jagalan Village, and the study was carried out for 3 consecutive days with a duration of 5–10 minutes using the HARS measuring instrument (Hamilton Anxiety Rating Scale). The level of anxiety in both respondents before doing five-finger hypnosis on Mrs. T and Mrs. Y is included in the moderate anxiety category. After carrying out five-finger hypnosis therapy on Mrs. T and Mrs. Y, they are in the category of mild anxiety. The application of five-finger hypnosis therapy is effective in reducing anxiety levels in pregnant women in Jagalan Village.